An Analysis of Ecranisation Process of Intrinsic Elements in Novel to Film œFive Feet Apart by Rachael Lippincott - Putri, Rizki Tania; Lubis, Fauziah Khairani; Manullang, Elisa Betty (TRANSFORM: Journal of English Language Teaching and Learning, 2021)
This study aims to determine the changes experienced by intrinsic elements found in the novel "Five Feet Apart" by Rachael Lippincott which was adapted into a film, along with the reasons. This study uses the descriptive qualitative method and Eneste's theory to analyze the changes that occur and the reasons for changes in the ecranisation study. The research data was taken from the intrinsic elements (plot, characters, and settings) of the Five Feet Apart novel published in 2018 and the Five Feet Apart film released in 2019. In data collection, the researcher used note-taking as an instrument to determine the reduction, addition, and modification and also the reasons for the after the novel was adapted into a film. In this study, the researcher found that there were several subtractions, additions, and modifications that occurred as a result of the ecranisation of the characters. While the plot and setting are only subject to reduction and modification, no additions are made to these two intrinsic elements. Also, the researcher found that the changes (reduction, addition, and modification) were caused by several reasons. The reasons that influence the change in the adaptation of a novel into a film are technical limitations, media differences in expressing the work, and the creativity of film makers.